توضیح القرآن کے محاسن کا تعارفی جائزہ: An introductory analysis of the merits of Tawdīḥ ‘l Qur’ān - Ahmad, Zaheer; Sana Ullah (FIKR-O NAZAR فکر ونظر, 2023)
Tawḍīḥ al Qur’ān is an Urdu translation of the holy Qur’ān by a well-known Muslim scholar Muftī Muḥammad Taqī ‘Uthmānī. Another name for this translation is Āasān Tarjumah-i Qur’ān (An Easy Qur’ānic Translation). The main aim of this article is to introduce and analyse this Qur’ānic translation and its merits. Tawḍīḥ al-Qur’ān contains a lot of merits, qualities and characteristics. This is inspired by and derived from the Urdu Qur’ānic translation of Shāh Abd al-Qādir Dihlavī. Its language is appropriate, simple, polite, and effective. The reader feels at home while reading this translation. The translator has used delicate words in this translation. The translator helped the readers understand the meanings of the Qur’ān by using simple wording. He successfully translated it eloquently, concisely, and briefly. The meaning, aim and purpose of the Qur’ānic text are depicted and highlighted in this Urdu translation. This is not a literal but expeditionary and contextual translation. However, the exposition is bracketed in many places to distinguish it from the translation. The translator explained it precisely which has enhanced its beauty and value. This translation is one of the best Urdu translations of the Qur’ān and is very helpful in learning the meaning of the Qur’ān in Urdu. In short, this translation possesses all the good qualities and merits which are necessary for an excellent translation. Because of these good qualities and merits, this translation is very popular and beloved by the masses irrespective of any discrimination of learning and intellectual level.